PENGARUH KOORDINASI TERHADAP PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK DI KECAMATAN PONTIANAK BARAT - Dian Putri Utami E.42008078 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The title of this research is “The Effect of Coordination to Electronic Identity Card Service in West Pontianak District”. This writing is supposed to know how much coordination, especially external coordination effected to Electronic Identity Card service in West Pontianak district. This is quantitative research with Product Moment Corelation formula. The result is, coordination has been run well and gave 3,24% effects to electronic Identity Card service in West Pontianak district. It could be categorized as low, therefore, researcher hopes there would be another researchers who could discover the other factors that possibly effecting electronic Identity Card service in West Pontianak district.Keywords: Effect, Coordination, and electronic Identity Card Service